2009
DOI: 10.1109/tasc.2009.2018213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Filament Diameter on ${\rm J}_{\rm e}$ in High Filament Count Bi2212/Ag Round Wire

Abstract: In this study, we investigated the effect of filament size on J e for high filament count Bi2212 round wire conductors partial melt processed with T max between 882 and 890 C in pure oxygen. The filament size that produced maximum J e was between 12 and 15 m depending on conductor design and T max . When the filament size was below 12 m the filaments were unstable during partial melt processing leading to a break-up in the structure of the filament array and low J e . This effect is attributed the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…While both Ag/Mg and Ag/Al can be produced in the DS condition by similar approaches, Al 2 O 3 has a higher elastic modulus and lower coefficient of thermal expansion (CTE) than MgO. Additionally, previous research has shown that Al 2 O 3 is relatively inert to Bi2212 and does not react strongly with the ceramic fiber used to insulate the conductor [42]. Lastly, Al is inexpensive and readily available [36,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While both Ag/Mg and Ag/Al can be produced in the DS condition by similar approaches, Al 2 O 3 has a higher elastic modulus and lower coefficient of thermal expansion (CTE) than MgO. Additionally, previous research has shown that Al 2 O 3 is relatively inert to Bi2212 and does not react strongly with the ceramic fiber used to insulate the conductor [42]. Lastly, Al is inexpensive and readily available [36,42].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research has shown that Al 2 O 3 is relatively inert to Bi2212 and does not react strongly with the ceramic fiber used to insulate the conductor [42]. Lastly, Al is inexpensive and readily available [36,42]. In the most recent report, Ag/0.5 wt%Al metal powder, which was oxidized at 675 • C in flowing pure oxygen, was used to form the DS Ag/0.5 wt%Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Ag-alloy sheathed Bi 2 Sr 2 CaCu 2 O x (Bi2212) superconductors produced via the powder-in-tube (PIT) process are promising for low temperature, high magnetic field applications and there is a significant effort to improve the critical current density (J c ) in round wires [1][2][3][4][5][6][7][8][9][10]. At present, Bi2212 wires are primarily heat treated using the partial melt process (PMP), which consists of heating the wire above its peritectic melt temperature, cooling to a temperature below T solidus , and isothermal annealing for an extended period [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…References [8]- [11] have shown that, because of the increased interface area which promotes greater c-axis texture, generally, increases with decreasing filament diameter up to a point, suggesting that there is an optimum filament size based on geometry. Reference [10] also suggests that the peak melt processing temperature must be adjusted for wire diameter and filament size to maximize .…”
Section: Introductionmentioning
confidence: 99%